A proteomic view of the host-pathogen interaction: The host perspective - Hartlova, Anetta; Krocova, Zuzana; Cerveny, Lukas; Stulik, Jiri (Proteomics, 2011)
The host-pathogen interaction represents a complex and dynamic biological system. The outcome of this interaction is dependent on the microbial pathogen properties to establish infection and the ability of the host to control infection. Although bacterial pathogens have evolved a variety of strategies to subvert host defense functions, several general mechanisms have been shown to be shared among these pathogens. As a result, host effectors that are critical for pathogen entry, survival and replication inside the host cells have become a new paradigm for antimicrobial targeting. This review focuses on the potential utility of a proteomics approach in defining the host-pathogen interaction from the host's perspective.
Keywords: proteom; proteomika; proteiny; bakteriální infekce; Host-Pathogen Interactions; Bacterial Infections; Proteomics; lidé; Proteome; Proteins; interakce hostitele a patogenu; Humans